Cities in 'multiple globalizations': insights from the upstream oil and gas World City Network. Issue 1 (1st January 2019) - Breul, Moritz
ABSTRACT: The role of cities in the global economy has been studied extensively for the specific case of advanced producer services. Only recently, studies started to broaden the analytical lens and explore the role of cities in 'multiple globalizations' by adding insights from other industries. Apart from showing that different World City Networks (WCNs) are characterized by differing spatial configurations, these studies are incapable of explaining why cities have been articulated into a particular WCN. Building on a case study of Singapore and Jakarta in the WCN of the upstream oil and gas industry, the study demonstrates the potential gained by adding flesh to the study of cities in 'multiple globalizations' through qualitative insights. The findings reveal how very different state roles have contributed to the shape of this particular WCN. The paper thereby illustrates how this recent field of research on cities in 'multiple globalizations' may advance beyond the mere description of city network structures.